Benzylpenicillin differentially conjugates to IFN-γ, TNF-α, IL-1β, IL-4 and IL-13 but selectively reduces IFN-γ activity - BROOKS, B M (Blackwell Publishing Inc, 2003)
It is known that β-lactam antibiotics can conjugate to lysine and histidine residues on proteins via the carbonyl group of the opened β-lactam ring. However, it is not known which proteins these drugs target and there is little work addressing whether conjugation is preferential for some proteins over others or if conjugation has functional consequences for the protein. We have previously shown that the β-lactam antibiotic benzylpenicillin (BP) conjugates to IFN-γ and reduces its activity. This interaction demonstrates selectivity, as BP does not bind to IL-4. Here, we extend our study to include other Th1 and Th2 cell-associated cytokines and two cytokines associated with inflammatory responses. We demonstrate by Western blotting that BP also conjugates to IL-1β, IL-2, IL-5, IL-13 and TNF-α but not to IL-10. Densitometric analysis of leading cytokine bands on blots revealed that IFN-γ always gave more intense BP-positive bands than any other cytokine analysed. Cytokines pre-incubated with BP at 37°C in a protein-containing, serum-free medium were assayed for their biological activity. By in vitro bioassay, BP inhibited the ability of IFN-γ but not IL-1β or TNF-α to induce CD54 expression on epithelial cells. In addition, BP did not affect IL-4 or IL-13 inhibition of mast cell proliferation. When the pre-incubation temperature was reduced to 4°C, BP did not conjugate to IFN-γ or modulate its activity. BP retained its inhibitory effect on IFN-γ activity when 20% FCS was added to the pre-incubation medium. In conclusion, BP conjugates to some cytokines but not others and this does not appear to be related to primary protein structure. Furthermore, of the cytokines studied, conjugation only to IFN-γ is accompanied by inhibition of activity. This phenomenon is temperature dependent and occurs in the presence of serum. These findings provide further evidence for differential, direct drug–cytokine interactions. Such interactions may have therapeutic implications in terms of targeting cytokines to regulate their activity.